THE MURAL OF ALFREDO ZALCE IN THE MICHOACAN REGIONAL MUSEUM (Tzintzun, Revista de Estudios Históricos, 2016)
This collaboration is an analysis of “The Defenders of National Integrity”, a muralpainted by Alfredo Zalce in 1951 which was funded by the Michoacan Museumand the National Institute of Fine Arts. The mural, which many critics consider tobe Zalce’s best, is located in the stairway of the Michoacan Regional Museum, andmeasures 135m². The objective of this study is not only from the perspective of itscomposition and theme but also from the trajectory of Zalce’s professionalism in thecontent of his works, of the ideas and pictorial influences he united, and of theinfluence of other Mexican muralists and other artists and writers affiliated withthe Writer and Artist’s Revolutionary League (LEAR) and the Popular GraphicsWorkshop (TGP).
Keywords: Alfredo Zalce; murals; LEAR; TGP